2007
DOI: 10.1080/09286580701375195
|View full text |Cite
|
Sign up to set email alerts
|

A Qualitative Study in the United Kingdom of Factors Influencing Attendance by Patients with Diabetes at Ophthalmic Outpatient Clinics

Abstract: Providing more complete information about diabetic retinopathy, and making eye clinic attendance more convenient for patients, may increase the number of diabetics who have regular eye examinations.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
75
1
3

Year Published

2010
2010
2023
2023

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 79 publications
(82 citation statements)
references
References 21 publications
3
75
1
3
Order By: Relevance
“…24 As part of routine patient education, there is a need to create greater awareness of the importance of retinopathy screening as well as explicitly highlighting the risk of asymptomatic disease and the risks of blindness. 23 The prevalence of retinopathy internationally varies widely, depending on methodology and the population sampled; however, the results of this study are in line with international estimates. The prevalence of retinopathy (any type) among people with diabetes in primary care in the UK was estimated to be 25%, 25 which is comparable to the results of this study.…”
Section: Comparison With Existing Literaturesupporting
confidence: 84%
See 1 more Smart Citation
“…24 As part of routine patient education, there is a need to create greater awareness of the importance of retinopathy screening as well as explicitly highlighting the risk of asymptomatic disease and the risks of blindness. 23 The prevalence of retinopathy internationally varies widely, depending on methodology and the population sampled; however, the results of this study are in line with international estimates. The prevalence of retinopathy (any type) among people with diabetes in primary care in the UK was estimated to be 25%, 25 which is comparable to the results of this study.…”
Section: Comparison With Existing Literaturesupporting
confidence: 84%
“…A qualitative study of the factors influencing attendance at ophthalmic outpatient clinics in the UK found that a lack of awareness of the severity of retinopathy was the main barrier to attendance. 23 A lack of knowledge about the need for screening was also identified as a barrier to attendance in Ireland. 24 As part of routine patient education, there is a need to create greater awareness of the importance of retinopathy screening as well as explicitly highlighting the risk of asymptomatic disease and the risks of blindness.…”
Section: Comparison With Existing Literaturementioning
confidence: 99%
“…Providing more complete information about DR, and making eye clinic attendance more convenient for patients may increase the number of diabetic patients having regular eye examinations. [32] Timely detection and treatment of DR is essential in preventing severe and moderate vision loss in diabetes mellitus. [33] Eye examination in diabetic is not to be restricted to search for retinopathy alone as they can also develop vision loss from other causes such as cataract and glaucoma.…”
Section: Discussionmentioning
confidence: 99%
“…Providing adequate information about the disease and its complications to those affected by diabetes as well as making screening more convenient (for example, by offering appointments after working hours) may increase the uptake of screening M A N U S C R I P T A C C E P T E D ACCEPTED MANUSCRIPT 19 programmes and reduce visual loss (Lewis et al, 2007). Furthermore, it is essential that patients identified as having sight-threatening retinopathy at screening programmes are referred timely to Hospital Eye Services; adequate patient pathways that allow urgent referral and treatment to be delivered, if required, need to be in place if the final goal of screening programmes, namely prevention of visual loss, is to be accomplished.…”
Section: B Screening For Diabetic Retinopathymentioning
confidence: 99%